First occurrence and description of Aceria fraxiniflora (Felt, 1906) Acariformes: Eriophyoidea) from Europe - Korda, M.; Csóka, Gy.; Szabó, Á.; Ripka, G. (Zootaxa, 2019)
Aceria fraxiniflora (Felt, 1906) is reported from Europe for the first time. This mite has never been described before and we therefore describe and illustrate the female and the nymph. The species was collected from the galled inflorescences and fruits of the introduced species Fraxinus pennsylvanica Marshall (Oleaceae) in Hungary, and from Fraxinus americana L. in Indiana, USA.